PENGARUH ALKALINITAS TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN LALAWAK Barbodes sp. [Effect of Alkalinity on the Survival Rate and Growth of Lalawak Fish, Barb odes sp.] - Yulfiperius Yulfiperius; Mozes R. Toelihere; Ridwan Affandi; Djadja Subardja Sjafei (Jurnal Iktiologi Indonesia, 2004)
This experiment was conducted to determine the effect of alkalinity on the survival rate and daily growth rate of Barbodes sp. The fishes were reared in 12 aquariums with four different alkalinity levels 48, 78, 108 and 138 ppm. Each aquarium filled with 10 fish at the average weight of 12.25 to 12.64 g attempt. The treatment lasted for 75 days. During the experiment, the fish were given commercial diet (pellet) with the dose of 5% of biomass weight at the frequency of three times a day. Result of the experiment showed that the survival rate for all treatments was 100%, while the alkalinity which suitable for daily growth rate of the fish was 80 ppm C’aCOr